Development of professional and ethical competence of primary school teachers in the system of professional development (Eurasian Research Bulletin, 2023)
Organization of the system of continuous professional development of pedagogic staff is the urgent task of today and the reforms implemented in the field of education are expanding more than ever. In this article, the author of the pedagogic staff, in order to increase the attention to the issue of education through the continuous professional development of the pedagogues, should work tirelessly to improve their professional and ethical competence, so that they can have a positive effect on the students. it is thought that it can be considered as a matching mechanism